Effect of paddy straw and sugarcane bagasse on growth and survival of giant freshwater prawn Macrobrachium rosenbergii (de Man, 1879) - Rajesh, Mridula; Manissery, J. K.; Rajesh, K. M. (Indian Journal of Fisheries, 2018)
Effect of artificial substrates on growth and survival of giant freshwater prawn Macrobrachium rosenbergii (de Man, 1879) in the nursery and grow-out rearing was evaluated. Nursery rearing was conducted for a period of 35 days in nine 1 m3 cement tubs with 15 cm soil base. Three tubs without substrates served as control (C) while three tubs each with 200 g of sugarcane bagasse (SB) or 200 g of paddy straw (PS) formed the treatments. Each tub was stocked with 15 post-larvae (mean weight, 0.01 g). Grow-out rearing was conducted for 90 days in six 25 m2 cement cisterns, of which three cisterns without substrate served as control (C) and three with 5 kg sugarcane bagasse (SB) served as treatment. Each cistern was stocked with 25 juveniles (mean weight, 0.55 g). The average phytoplankton and zooplankton abundance in water as well as algae and food organisms attached on the substrate in the nursery phase was greater in bagasse than in paddy straw treatments. Addition of substrate resulted in higher growth and survival both in nursery and grow-out phase. Prawns grown in cisterns provided with substrates were of more uniform size than those in control cisterns. The study recommends the use of substrate based aquaculture for nursery and grow-out rearing of M. rosenbergii.